2008
DOI: 10.1111/j.1460-9592.2008.02652.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma B‐type natriuretic peptide monitoring to evaluate cardiovascular function prior to organ procurement in patients with brain death

Abstract: Assays of plasma BNP concentrations have been shown to be helpful in differentiating myocardial dysfunction from primary lung disease in both the adult and pediatric population. However, our data demonstrate that mechanisms other than myocardial performance may regulate BNP levels in patients with severe central nervous system injury who progress to brain death. Our preliminary data suggest that these assays appear to be of limited value in assessing myocardial performance in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Several small studies of both pediatric and adult donors have failed to demonstrate the utility of BNP and NT‐proBNP values in predicting recipient outcomes but some have shown weak correlations with early myocardial dysfunction …”
Section: Donor Troponin and Other Biomarkersmentioning
confidence: 99%
“…Several small studies of both pediatric and adult donors have failed to demonstrate the utility of BNP and NT‐proBNP values in predicting recipient outcomes but some have shown weak correlations with early myocardial dysfunction …”
Section: Donor Troponin and Other Biomarkersmentioning
confidence: 99%
“…In order to expedite the process and eliminate the need for invasive procedures, Lieppman et al measured BNP values in a cohort of 8 patients, ranging in age from 6 months to 21 years, after the proclamation of brain death. 41 The diagnosis of brain death by clinical or radiological examination had been completed in all patients and the patients were scheduled for organ procurement. Myocardial contractility as assessed by echocardiography was within normal limits.…”
Section: Diagnostic Applications Of Plasma Bnp Monitoringmentioning
confidence: 99%
“…In a small pediatric series (n ϭ 8), cardiac allografts of donors with BNP levels above the upper limit were shown to be acceptable and with a good function after transplantation. 7 In contrast, in one recent study, Amir et al showed that BNP levels were lower in organ donors (n ϭ 12) whose hearts were considered acceptable for transplantation, compared with those having unsuitable hearts. 8 However, they could not show a relation between BNP levels and a combined end-point of sub-optimal outcome of the recipient (death, prolonged inotropic support and prolonged hospitalization).…”
Section: Discussionmentioning
confidence: 86%